Sintomatología depresiva y calidad de vida en estudiantes de medicina en alta latitud sur - Alvarado-Aravena, Caren; Estrada Goic, Claudia Andrea; Nuñez Espinosa, Cristian Andrés (My University, 2021)
Background: There is no evidence for the association of depressive symptoms with the sense of well-being of undergraduate medical students residing in high southern latitudes (HSL). Aim: To assess the frequency of depressive symptoms and its relationship with seasonal sensitivity and quality of life in medical students residing in HSL. Material and Methods: The Beck anxiety and depressive symptoms inventory, the seasonal pattern assessment questionnaire and the quality-of-life questionnaire of the WHO were applied to 102 medical students residing in Magallanes, Chile. Results: Fifty-two percent of respondents reported some degree of depressive symptoms. These symptoms were significantly associated with the seasonal pattern score (r = 0.432, p < 0.01). They were also inversely associated with parameters of physical health and psychosocial health (r = -0.567, p < 0.01 and r = -0.708, p < 0.01, respectively). There was also a correlation between depressive and anxiety symptoms. Conclusions: Depressive symptoms are common in medical students residing in HSL and they are associated with seasonal sensitivity and quality of life measures.
Keywords: None